Predicting the shape formation of hollow parts with a flange in the process of combined radial-reverse extrusion - Hrudkina, Natalia; Aliieva, Leila; Markov, Oleg; Marchenko, Irina; Shapoval, Alexander; Abhari, Payman; Kordenko, Mariia (Eastern-European Journal of Enterprise Technologies, 2020)
The simulation of the process of combined radial reverse extrusion of hollow parts with a flange has established two fundamentally different, in terms of the components of the kinematic modules, calculation schemes CDZ-1.i and CDZ-2.j, taking into consideration the possible shape of the boundary of the section of a metal flow inside a workpiece. The comparison of the dependences of the optimal relative rate of metal outflow in the opposite direction for different schemes indicates significant differences in the resulting values in the course of the deformation process. The relevance of this study is due to making it easier to evaluate the use of the combined extrusion process to produce hollow parts with a flange while maintaining the required dimensions compared to simple deformation schemes. We have identified the lack of detailed studies into the technologies for the introduction of combined extrusion schemes, as well as the absence of technological recommendations for determining the force regime and the shape formation of a semi-finished article. The process of the combined extrusion of hollow parts with a flange was investigated, thereby selecting different types based on the nature of the metal flow depending on the geometric ratios of the deformation process. We have obtained experimental data on the gradual shape formation of a semi-finished product in the process of deformation at different geometric ratios. The limits of using estimation schemes of the process have been defined to obtain data on the increments in a semi-finished product, including in terms of predicting the formation of a shrinkage cavity in the bottom part. It is recommended that a condition of selecting the appropriate scheme should be the condition for a minimum value of the reduced pressure of deformation ̅pi< ̅pj. The resulting recommendations make it easier to predict the shape formation and the force mode of extrusion (a deviation from experimentally obtained data can be reduced to 10 %), which would contribute to evaluating the rationality of the combined extrusion processes while ensuring the required dimensions of a part